NEGOTIATING SAKINAH IN THE DIGITAL ERA: MARRIAGE PRACTICES OF GENERATION Z IN LEPELLE VILLAGE ROBATAL DISCTRICT - Uswatun Hasanah; Mujiburrohman Mujiburrohman (Universitas Nurul Jadid, 2026)
This study examines the marriage practices of Generation Z in realizing a sakinah family in Lepelle Village, Robatal District, within the context of digital transformation. Using a qualitative approach with an empirical socio-legal perspective, data were collected from 15 informants through interviews, observation, and documentation, and analyzed using thematic analysis. The findings reveal a growing trend of early-age marriage driven by socio-religious norms and digital influence, diverse interpretations of the sakinah family combining religious and modern values, and multidimensional challenges, particularly economic, psychological, and socio-digital factors. Digital media plays an ambivalent role, acting as both a source of guidance and pressure. This study proposes the concept of “negotiated sakinah family formation,” highlighting that family realization is shaped by the interaction of normative, structural, and digital dimensions. The study contributes to bridging normative Islamic family law and empirical social realities in the digital era.